Low skeletal muscle mass as a proxy marker of sarcopenia is a risk factor for major complications in older patients undergoing curative colon resections for colon cancer - Tırnova, İsmail; Gasimova, Maya; Akay, Hatice; Sarıtürk, Çağla; Güven Mert, Aslıhan; Yenidünya, Özlem; Karakayalı, Feza Yarbuğ (Frontiers in Medicine, 2025)
IntroductionVarious reports have confirmed that low skeletal muscle mass, a proxy marker of sarcopenia, can be a risk factor for surgical and oncological outcomes in colon cancer. We aimed to investigate the effects of skeletal muscle mass index (SMMI) on postoperative complications, overall survival (OS), and disease-free survival (DFS) in older patients with colon cancer who underwent elective curative colon resections.Materials and methodsPatients over 65 years old with stage I-III colon cancer who underwent elective curative colon resections between January 2015 and December 2023 were included in this single-center retrospective longitudinal study. Demographics, comorbidities, laboratory data, pathological features, malignant lymph node ratio (MLNR), OS, and DFS were recorded. Controlling Nutritional Status (CONUT) Score was used to assess the nutritional status. An axial portal-phase image was obtained at the level of the third lumbar vertebra, and muscle areas were calculated. SMMI was calculated by dividing the muscle area (cm2) by the square of the patient’s height (m2). Low SMMI was defined as SMMI<41 cm2/m2 in women and < 43 cm2/m2 in men with body mass index (BMI) <25 kg/m2, and as SMMI <53 cm2/m2 in patients with a BMI >25 kg/m2. Postoperative complications were classified according to the Clavien-Dindo system. Univariate and multivariate analyses were performed to investigate the factors related to the postoperative complications, OS and DFS.ResultsIn total, 98 cases (mean age 75.2 ± 6.9, 55.1% male) were included in the study. The median follow-up time was 38.3 (0.5–113) months. There were 64 patients (65.3%) in the Low SMMI group and 34 patients (34.7%) in the Normal SMMI group. Logistic regression analysis demonstrated that low SMMI was associated with a higher risk of major complications, with an odds ratio of 5.3 (95% CI, 1.1–20.1; p = 0.037). Cox regression analysis revealed no significant differences in OS and DFS.ConclusionLow SMMI as a proxy marker of sarcopenia was found to be an independent risk factor for postoperative major complications. Additional prospective studies are warranted to obtain more reliable results.